The Role of Anti-Plague Institutions in Provision of the Epidemiological Well-Being During the Preparation and Carrying out of the APEC 2012 Summit - S. V. Balakhonov; E. I. Andaev; M. V. Chesnokova; A. V. Allenov; T. V. Khomenko; L. I. Ivanov; A. Ya. Nikitin; S. A. Kosilko; A. G. Koval’Sky; E. S. Kulikalova (Проблемы особо опасных инфекций, 2013)
Summarized are the results of the work on provision of sanitary and epidemiological well-being during the arrangement and carrying out the APEC Summit on the Russky Island. The set of organizational and prophylactic measures aimed at prevention of potential danger of emergency situation of sanitary and epidemiological character is presented. Measures on provision of epidemiological well-being of the participants and guests of the APEC Summit, based upon interaction of the regional plague-control institutions with anti-epidemic and health services of the Primorsky Region, demonstrated their efficiency. Epidemiological situation on the Russky Island and Vladivostok city was safe. The materials presented can be used to develop a set of measures ensuring the epidemiological well-being during large scale political and economic events holding at the national and international levels.